Influence of plasticiser type and nanoclay on the properties of chitosan-based materials. (5th February 2021) - Chen, Pei; Xie, Fengwei; Tang, Fengzai; McNally, Tony
Graphical abstract: Highlights: Chitosan and chitosan/carboxymethyl cellulose (CMC) composites processed. MMT nanosheets influence biopolymer properties, dependent on plasticiser type. Hydrophilic plasticisers may reduce the surface hydrophilicity of biopolymer films. Plasticiser and MMT vary the availability of polar groups on biopolymer surface. Biopolymers with tailored surface wettability useful for biomedical applications. Abstract: Chitosan, a biocompatible polysaccharide having antimicrobial efficacy, is highly useful for biomedical and other applications. How chitosan properties can be tailored continues to attract intense research interest. Herein, chitosan and chitosan/carboxymethyl cellulose (CMC) materials filled with montmorillonite (MMT) were thermomechanically processed resulting in excellent nanoclay dispersion. Inclusion of MMT significantly increased molecular relaxation temperatures, tensile mechanical properties, and film surface hydrophobicity. When plasticisers such as 1-ethyl-3-methylimidazolium acetate ([C2 mim][OAc]) or glycerol were introduced, the effect of MMT on the biopolymer properties largely depends on whether the MMT alters plasticiser–biopolymer interactions. [C2 mim][OAc]-plasticised chitosan exhibited a relatively high contact angle (100 ± 7°) similar to the un-plasticised chitosan/MMT material, derived from the strong hydrogen-bonding capability of [C2 mim][OAc]. Polyelectrolyte complexation (PEC) allowed the glycerol-plasticised chitosan/CMC material to have a hydrophobic surface (contact angle: 90 ± 6°) similar to that of the un-plasticised chitosan/CMC/MMT material. Specifically, further inclusion of MMT interrupted biopolymer–plasticiser interactions, leading to increased surface wettability. However, while addition of [C2 mim][OAc] resulted in reduced hydrophilicity of the chitosan/CMC matrix, addition of MMT counteracted this effect by interacting with the IL. This work shows the plasticisers and MMT influence surface hydrophilicity mainly by determining the availability of free biopolymer polar groups.